2011
DOI: 10.1038/ejcn.2011.208
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-lowering properties of different pectin types in mildly hyper-cholesterolemic men and women

Abstract: Background/Objectives: Viscous fibers typically reduce total cholesterol (TC) by 3-7% in humans. The cholesterol-lowering properties of the viscous fiber pectin may depend on its physico-chemical properties (viscosity, molecular weight (MW) and degree of esterification (DE)), but these are not typically described in publications, nor required by European Food Safety Authority (EFSA) with respect to its generic pectin cholesterol-lowering claim. Subjects/Methods: Here, different sources and types of well-charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(122 citation statements)
references
References 30 publications
2
113
0
7
Order By: Relevance
“…There are only few studies that have compared bioavailability or health effects between pectin with different chemical characteristics (DP and DM), source, and type. Citrus pectin sources (high DM and high MW) exerted greater LDL cholesterol-lowering properties than low DM and low MW of citrus pectin and high DM of orange pulp fiber [29]. However, Judd and Truswell [30] reported that LMP has similar cholesterol-lowering effects compared to HMP.…”
Section: Characteristic Of Samplesmentioning
confidence: 92%
“…There are only few studies that have compared bioavailability or health effects between pectin with different chemical characteristics (DP and DM), source, and type. Citrus pectin sources (high DM and high MW) exerted greater LDL cholesterol-lowering properties than low DM and low MW of citrus pectin and high DM of orange pulp fiber [29]. However, Judd and Truswell [30] reported that LMP has similar cholesterol-lowering effects compared to HMP.…”
Section: Characteristic Of Samplesmentioning
confidence: 92%
“…Quim. 2018, 47 (2), [5][6][7][8][9][10][11] Los productos utilizados en el trabajo (arepa sin pectina, arepa con 10% (p/p) de pectina cítrica comercial y arepa con 10% (p/p) de pectina de curuba) fueron sometidos al siguiente análisis proximal: humedad (método AOAC 930.15) (16), cenizas (método AOAC 942.05) (17), grasa total (método AOAC 920.39) (17), proteína (método AOAC 920.152) (17), fibra dietética total, soluble e insoluble (Kit Sigma TDF100A, método AOAC 991.43) (17) y carbohidratos determinados por diferencia. Las muestras se procesaron por triplicado en todos los casos.…”
Section: Voluntariosunclassified
“…Cuando se consume pectina de forma regular, se obtiene un efecto benéfico en la salud ya que disminuye los niveles séricos de lípidos y glucosa, ayudando a prevenir enfermedades como diabetes y dislipidemias (6)(7)(8). Estas propiedades hacen a la pectina idónea para enriquecer en fibra soluble alimentos de alto consumo, como la arepa de maíz, en grupos poblacionales donde los carbohidratos prevalecen en la dieta diaria debido a su bajo costo y fácil disponibilidad.…”
Section: Introductionunclassified
“…Гиперхолестеринемия, профилактика сердечно-сосу-• дистых заболеваний и метаболического синдрома [53][54][55][56][57]. Синдром холестаза [58,59].…”
Section: педиатрическая фармакология /2012/ том 9/ №unclassified